Utilization of coconut coir waste products: environmental and economic education efforts for Kertaharja Villagers - Zia Ramadan; Nia Kurnia; Devi Anggrayni; Nadzira Al Mahira Zahra; Alya Indriyani; Tendi Setiadi; Irfan Fauzi; Gunawan Refiadi (Community Empowerment, 2023)
Kertaharja is the largest coconut producing village in Cimerak District, Pangandaran. 35% of the weight of coconuts will be waste in the form of coconut coir. Unfortunately, Kertaharja residents do not know about this waste product that has economic value and can become an environmentally friendly growing medium. Therefore, this Community Service activity is aimed at educating the environment and the family economy with the respective targets being children of SDN 2 Kertaharja and residents of Kertaharja Village. The environmental education method uses pre-test and post-test with cocopeat material as an environmentally friendly growing medium, while economic education uses the economic opportunity seminar method from coconut coir waste. The results of the activity show that environmental education has increased students' understanding of SDN 2 Kertaharja on cocopeat growing media. Meanwhile, economic education has increased the interest of Kertaharja residents to utilize coconut coir waste as an opportunity for additional family income.